1996
DOI: 10.1111/j.1440-1746.1996.tb01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte volume as an indicator of hepatic functional reserve in cirrhotic patients with liver tumours

Abstract: Using computed tomography (CT), measurements of whole liver volume have been used for the assessment of pre-operative functional reserve in cirrhotics. However, measurements of hepatocyte volume, which exclude stromal fibrous tissue, are considered to more directly reflect hepatic functional reserve. We investigated the relationship between total hepatocyte volume and each of the parameters of conventional liver function. Indocyanine green (ICG) tests and blood analyses for the assessment of liver function wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…I\R injury could reduce the rate of excretion of ICG via several different mechanisms. For example, cellular microtubule damage can lead to the subsequent impairment of ICG removal from hepatocytes into bile canaliculi [35] and hepatocyte necrosis [36], as ICG clearance is correlated significantly with hepatocyte volume, which indicates the hepatic functional reserve [37]. Also, ICG removal can be reduced secondary to a decrease in cellular ATP levels after reperfusion [38,39], resulting in the impairment of bile excretion [39].…”
Section: Discussionmentioning
confidence: 98%
“…I\R injury could reduce the rate of excretion of ICG via several different mechanisms. For example, cellular microtubule damage can lead to the subsequent impairment of ICG removal from hepatocytes into bile canaliculi [35] and hepatocyte necrosis [36], as ICG clearance is correlated significantly with hepatocyte volume, which indicates the hepatic functional reserve [37]. Also, ICG removal can be reduced secondary to a decrease in cellular ATP levels after reperfusion [38,39], resulting in the impairment of bile excretion [39].…”
Section: Discussionmentioning
confidence: 98%
“…In a study of 40 patients, a reduction in mean liver volume over time has been noted in nonsurvivors versus an actual increase in mean liver volume in survivors. Matsui et al found that liver volume per unit body weight correlated well with functional reserve in cirrhotic patients with liver tumors [2].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is one organ where numerCorrespondence to: K. K. Kopecky ous attempts have been made to employ imaging techniques to make quantitative volumetric measurements. Measurements of liver volume have been used to make surgical decisions regarding hepatic resection or transplantation, to plan radiotherapy dosimetry, to assess the progress of various diseases, and to assess responses to treatment [1][2][3][4][5][6][7][8][9][10][11]. Most of the studies to date have been performed with conventional computed tomography (CT) after intravenous administration of iodinated contrast material, and some were performed after intra-arterial administration of iodinated contrast material (CT arterial portography).…”
mentioning
confidence: 99%
“…32,37 One of the reasons for this lower resection rate is that the large amount of sacrificed nontumorous liver restricts the surgical indication for patients with HCC, especially for those with cirrhosis, to avoid postoperative liver failure. 15,18,20,38,39 If surgeons consider the nomargin resection as a surgical option, patients with HCC who were previously deemed to have an unresectable form of the disease might be good candidates for curative resections, resulting in a higher resection rate. Kaplan-Meier estimates of the no-recurrence (A) and overall survival (B) rates of patients with hepatocellular carcinoma after hepatic resection.…”
Section: Commentmentioning
confidence: 99%